2022
DOI: 10.1111/oik.09126
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the sickest: selective predation differentially modulates ecological and evolutionary disease dynamics

Abstract: Predators and parasites are critical, interconnected members of the community and have the potential to shape host populations. Predators, in particular, can have direct and indirect impacts on disease dynamics. By removing hosts and their parasites, predators alter both host and parasite populations and ultimately shape disease transmission. Selective predation of infected hosts has received considerable attention as it is recognized to have important ecological implications. The occurrence and consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…However, predators sometimes preferentially avoid consuming infected prey (Flick et al, 2016), for example, a study on black‐capped chickadees and downy woodpeckers found that they tended to avoid misshapen galls and unhealthy larvae, even during periods of food limitation (Schlichter, 1978). Indeed, a recent synthesis suggests that selective predation on uninfected individuals is more common than generally acknowledged (Gutierrez et al, 2022). In their original formation of the healthy herd hypothesis, Packer et al (2003) noted that this type of selective predation should cause predators to increase parasitism in their prey.…”
Section: Selective Predationmentioning
confidence: 99%
“…However, predators sometimes preferentially avoid consuming infected prey (Flick et al, 2016), for example, a study on black‐capped chickadees and downy woodpeckers found that they tended to avoid misshapen galls and unhealthy larvae, even during periods of food limitation (Schlichter, 1978). Indeed, a recent synthesis suggests that selective predation on uninfected individuals is more common than generally acknowledged (Gutierrez et al, 2022). In their original formation of the healthy herd hypothesis, Packer et al (2003) noted that this type of selective predation should cause predators to increase parasitism in their prey.…”
Section: Selective Predationmentioning
confidence: 99%